International Webinar - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN,12 June 2021 - This international webinar on 'Peluang dan Implementasi Keuangan Digital di Era New Normal 2021' had been held virtually through Zoom Application.